3D Aerogel of Graphitic Carbon Nitride Modified with Perylene Imide and Graphene Oxide for Highly Efficient Nitric Oxide Removal under Visible Light. Issue 19 (10th April 2018) - Hu, Jundie; Chen, Dongyun; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Lu, Jianmei
Abstract: 3D materials are considered promising for photocatalytic applications in air purification because of their large surface areas, controllability, and recyclability. Here, a series of aerogels consisting of graphitic‐carbon nitride (g‐C3 N4 ) modified with a perylene imide (PI) and graphene oxide (GO) are prepared for nitric oxide (NO) removal under visible‐light irradiation. All of the photocatalysts exhibit excellent activity in NO removal because of the strong light absorption and good planarity of PI–g‐C3 N4 coupled with the favorable charge transport properties of GO, which slow the recombination of electron–hole pairs. The aerogel containing thiophene displays the most efficient NO removal of the aerogel series, with a removal ratio of up to 66%. Density functional theory calculations are conducted to explain this result and recycling experiments are carried out to verify the stability and recyclability of these photocatalysts. Abstract : 3D aerogels constituted by graphitic carbon nitride modified with perylene imides and graphene oxide are fabricated successfully for highly efficient nitric oxide removal (600 ppb) under visible light irradiation, especially the aerogel containing thiophene displays the best photocatalytic effect. All these results are consistent with density functional theory calculations. Importantly, the macroscopic aerogels have stability and recyclability.